Implementasi PendidikanKarakter bagi Siswa di Era Digitalisasi - Ika Usmalia Ibrahim (Jurnal Dirosah Islamiyah, 2023)
The era of digitalization has had many impacts on various things, one of which is changing the character of students. Therefore, strengthening character education is an important thing to do at this time. The five central character values are religion, nationalism, independence, cooperation and integrity. Wherever the basic values of character education begin, both individuals and universities need to develop these core values conceptually and operationally. Character education teaches habits of thought and behavior so that they can live and work together with their families, communities and countries and help them make the right decisions. Because character education cannot be formed instantly, students must be trained seriously, continuously and in a balanced way to achieve ideal character. Keywords: Character education, character change, way of thinking.